Efficacy of the BATMAN Score in Predicting Functional Outcomes After Thrombectomy for Basilar Arterial Occlusion: A Frequentist and Bayesian Meta-Analysis - Huang, Ho-Chang; Lin, Hui-An; Wang, Jyun-Jhe; Lin, Sheng-Feng (American Journal of Neuroradiology, 2025)
BACKGROUND: The Basilar Artery on Computed Tomography Angiography (BATMAN) score is a 10-point grading system assessing arterial opacification and thrombus burden in the posterior circulation. It predicts outcomes in endovascular thrombectomy, with lower scores reflecting poor opacification.PURPOSE: This systematic review and meta-analysis evaluated the BATMAN score’s efficacy in predicting 90-day functional outcomes after thrombectomy.DATA SOURCES: We systematically searched PubMed, EMBASE, Scopus, and Cochrane Library and adhered PRISMA guidelines for relevant English and Chinese articles published between January 1, 2017, and December 1, 2024.STUDY SELECTION: The inclusion criteria were as follows: including patients who had undergone endovascular therapy (EVT) for posterior circulation acute ischemic stroke; assessing the BATMAN score through angiographic examinations, such as CTA, DSA, and MRA before EVT; and assessing functional outcomes on day 90 by using the mRS. We excluded duplicate articles, conference summaries, review articles, articles lacking original data, and articles for which the full text was unavailable.DATA ANALYSIS: We determined the standardized mean difference in BATMAN scores between patients with favorable and unfavorable outcomes. Binormal receiver operating characteristic curve analysis determined the BATMAN score’s diagnostic performance and the optimal threshold. The Bayesian approach validated the mean between-group difference in the BATMAN scoresDATA SYNTHESIS: A higher BATMAN score was significantly associated with a favorable functional outcome (standardized mean difference in Cohen’s d: 0.82; 95% CI: 0.56–1.08). Binormal receiver operating characteristic curve analysis revealed an optimal BATMAN score threshold of ≥6, indicating a sensitivity of 76.1%, a specificity of 52.0%, and an area under the curve value of 0.71 (95% CI: 0.69–0.73). The Bayesian estimate of the mean between-group difference in BATMAN score was 1.52 (95% highest posterior density: 1.41–1.62).LIMITATIONS: All of the included studies were observational in design and varied in terms of sample size. Nonetheless, our comprehensive statistical approach, with both frequentist and Bayesian approaches, might have overcome the limitations associated with sample size discrepancies.CONCLUSIONS: Our findings suggest the BATMAN score of ≥6 predicts post-thrombectomy favorable functional outcomes in patients with posterior circulation acute ischemic stroke.ABBREVIATIONS: BATMAN = Basilar Artery on Computed Tomography Angiography; EVT = endovascular therapy.